Peran Kepercayaan dalam Mempengaruhi Hubungan E-WOM dan Citra Merek terhadap Keputusan Pembelian di Marketplace - Rizki, Heri; Fitri, Aida; Andi, Muhammad (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the role of consumer trust in mediating the influence of electronic word of mouth and brand image on the review of purchasing decisions on the Shopee e-marketplace in Banda Aceh City. This research method uses a quantitative approach with a sample of 115 respondents through a purposive sampling technique. The data of this study were collected through a questionnaire and analyzed using SEM AMOS. This study concludes that e-wom and brand image are proven to be able to increase consumer trust and purchasing decisions on Shopee in Banda Aceh City. In addition, trust also helps increase consumer decisions in purchasing various products offered by Shopee. Consumer trust in this study is proven to partially mediate e-wom and brand image on Purchase decisions on Shopee in Banda Aceh City.